Aksesibilitas Pusat Rekreasi: Pengalaman dan Harapan Bagi Penyandang Disabilitas Fisik di Kota Kupang - Delsiana Maya Zeldis W.L; Angelika M. Tokan; Jessica V. Otemusu; Darling D. Manubulu; Avrillia G.H Leo Radja; Pasifikus Ch. Wijaya; Marleny P. Panis (JURNAL ILMIAH NUSANTARA, 2026)
Every individual requires recreation/entertainment as a secondary need that must be fulfilled. Adequate access is a primary factor in creating comfort and increasing public interest in visiting recreation centers. However, inadequate access poses a barrier for persons with physical disabilities in fulfilling this need. The participants in this study consisted of eight individuals with physical disabilities, specifically meeting the criteria of being wheelchair or crutch users in Kupang City. The purpose of this research is to address the various barriers experienced by persons with disabilities in accessing facilities at recreation sites. The data collection process in this study was conducted through in-depth interviews with the participants. This study employs a qualitative method with a descriptive and critical approach. The results indicate seven themes that explain how accessibility in recreation centers is not yet available, making individuals with physical disabilities feel neglected and marginalized. This, of course, affects the comfort and safety of the participants' experiences during their visits.